Do the Poor Benefit from Corporate Social Responsibility? A Theory-Based Impact Evaluation of Six Community-Based Water Projects in Sri Lanka - Wilhelm Löwenstein; Martina Shakya; Marc Hansen; Sanjay Gorkhali (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2015)
Corporate Social Responsibility (CSR) can work as an effective means towards minimising business risk and maintaining amicable relationships with diverse groups of stakeholders. While many studies have examined the impacts of CSR on firm value and customer perceptions, little is known about the effects of a philanthropic engagement of the private sector on external stakeholder groups, such as local communities in developing countries. This paper examines welfare effects of six community-based water supply projects that were supported by a thermal power plant in Sri Lanka as part of the company's CSR strategy. The implications of these CSR activities are analysed from the perspective of the project beneficiaries, the majority of them poor smallholder farmers. Household production and labour income functions are estimated from survey data to analyse two pathways through which the water projects affect the beneficiaries' lives. First, the households get individual access to water that allows for the irrigation of home gardens, increases land productivity and changes households' farm output and income (irrigation channel). Second, the projects have an indirect effect on households' income via a time channel, i.e. the effect that due to the individual water access the households save time as there is no need any more to fetch water from far away water bodies or wells. This allows for a reallocation of labour time for other productive income-generating activities. Despite the considerable costs that households have to bear for an individual water connection, the study finds a systematic, positive net income effect of the projects on the beneficiaries via both the irrigation and the time channel. Qualitative evidence supports these findings and also reveals additional positive, non-monetarised project impacts. As the water projects would not have been realised without the subsidiary financial support of the power plant, it is concluded that the company's CSR engagement is increasing the welfare of the beneficiary communities.
Keywords: 330; Corporate Social Responsibility; Productivity Method; Theory-based Impact Evaluation; Club Goods; Stakeholder; Smallholder Farmers; Community-Based Water Supply; Sri Lanka; Welfare Changes; Wasserversorgung; Entwicklungsprojekt; Corporate Social Responsibility; Wirkungsanalyse; Clubtheorie; Stakeholder; Wohlfahrtsanalyse; Ländlicher Raum; Sri Lanka